If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-7=2(x-7)-(x-7)
We simplify the equation to the form, which is simple to understand
x-7=2(x-7)-(x-7)
Reorder the terms in parentheses
x-7=+(+2x-14)-(x-7)
Remove unnecessary parentheses
+x-7=+2x-14-(+x-7+)
Remove unnecessary parentheses
x-7=+2x-14-1x+7
We move all terms containing x to the left and all other terms to the right.
+1x-2x+1x=-14+7+7
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 6(2+x)=5(1-4x) | | 5(4x+3)=18 | | 8w=.25 | | 8b^4(6b^5+10b)= | | y^2-37-4= | | 8w= | | 11(z+1)-3(z-1)=3(z-4)+4(z-1) | | 9x+8=5-(7x-8) | | -2v=.75 | | 0.3u-0.1=2.2u-5.8 | | 4(x+3)-1=27 | | x^2+5x=6whatisx | | -200=2(10x+10) | | 5x^2+x-14=-10 | | 9y^2-y+6=0 | | v^2-6v-7= | | X^3-2x^2-16x+32= | | 4x+8y=4slope | | 6x+7=(x+8) | | (x-3)(x+8)=0whatisx | | 6a-4whena=5 | | 1.7m^2=6.5n-4n+2.5m^2-n | | 8(7x-7)=45 | | 5-7(4x+6)=2 | | -6=-6v+4(v-6) | | (5w-8)(2w+9)=0 | | Ys+yz=tfory | | z+1.4z-1.6=1.5(z+1.4) | | 0=4v-6 | | 3m+8=3(4+m)-8 | | z+1.4z= | | 4(c+1)+c= |